Ocorrência de integrons em amostras de Escherichia coli diarreiogênica e espécimes fecais de crianças com e sem doença diarreica - Patrícia Luciana de Oliveira (2017)
Escherichia coli is a highly diverse species both phenotypically and genotypically. Two groups may be clearly recognized, one of them comprising those strains that are members of the indigenous microbiota and the other one gathering exogenous microorganisms. E. coli is frequently implicated in the etiopathogenesis of healthcare associated infections as well as community acquired infections. Among them acute diarrhea should be highlighted. Antimicrobial drug resistance is considered as a public health problem. The property is commonly acquired via mobile genetic elements such as gene cassettes. These units are frequently inserted into integrons defined as genetic elements that allow efficient capture and expression of exogenous genes. This study aimed at characterizing integrons and gene cassettes in diarrheagenic E. coli (DEC) and E. coli isolates from the indigenous microbiota (EEC). We also evaluated the presence of integronsin fecal specimens of children with or without diarrhea. The study group included 170 E. coli isolates [92 DEC (57 ETEC and 41 EPEC) and 72 EEC] and 40 fecal specimens obtained from children with (20) and without (20) diarrhea. PCR was employed to search for classes 1, 2, and 3 integrons and then positive isolates were employed for gene cassettes investigation. Gene cassettes amplicons were sequenced in order evaluate the occurrence of genes coding for antimicrobial resistance. Additionally the antimicrobial susceptibility profile of E. coli isolates was determined.Classes 1 and 2 integrons were detected in 20.6% and 7.1% of the bacterial strains, respectively. Both classes of integron were detected simultaneously in 2.4% of the isolates. The detected frequency of integrons and antimicrobial resistance in EEC arises great concerns. No class 3 integron was detected. Gene cassettes were observed in the majority (71.4%) and in all strains positive for class 1 and 2 integrons, respectively. Genes that code for βlactams, streptomycin, spectinomycin, trimetoprim, and steptotrycin were detected. Fecal specimens were assayed by qPCR in order to quantify Bacteria, int1, int1 clínico, andint2. Regardless the study group (children with or without diarrhea) about 109 copies of each integron marker by gram of feces were detected. Integrons were detected in all fecal specimens. Taken together our results highlight the importance of integrons and of the indigenous microbiota as a reservoir and in the dissemination of antimicrobial resistance reinforcing the need for designing protocols aiming to control this process.